Beyond one-size-fits-all: differentiating market access measures for commodity systems in the Kenyan highlands - Baltenweck, Isabelle; Staal, Steven J. (Wiley, 2007)
Market access measures employed by economists and spatial analysts may not adequately capture local market or product-specific variation. Analysis is conducted on the effects of market access on two commodities in the Kenyan highlands: milk and bean seeds. Both simple and composite measures of market access are applied to spatial price formation models to create spatial price decay functions in the context of household-specific transaction costs. Composite measures of market access include negative exponential (using travel time or distance as cost) and gravity measures. The results demonstrate that the effects of market access differ significantly depending on the particular goods of interest. Simple measures of market access have the advantage of being more easily interpretable, and should therefore be preferred when communicating research outputs to the non-scientific community, especially decision-makers. The implications are that research addressing commodity-specific development questions needs to look beyond generic measures of market access and develop tailored measures that reflect the characteristics of the commodity system of interest. The analysis also demonstrates that spatial price formation can be used to generate potentially more accurate measures of unit-distance marketing costs.